Assessment of Some Heavy Metals in Drinking Water Samples of Tunceli, Turkey - Olcay Kaplan; Nuran Cikcikoglu Yildirim; Numan Yildirim; Nilgun Tayhan (E-Journal of Chemistry)
The drinking water quality is associated with the conditions of the water supply networks, the pollution and the contamination of groundwater with pollutants of both anthropogenic and natural origin. In this study, water samples were taken from four different waterworks in Tunceli, Turkey and heavy metals concentrations (As, Cu, Cd, Cr, Pb, Ni and Hg) were measured. Four sampling sites were pre-defined in different locations of the city. The obtained results showed that, the heavy metals concentrations in water samples did not exceed the values of WHO (World Health Organization), EC (Europe Community), EPA (Environment Protection Agency) and TSE-266 (Turkish Standard) guidelines.